2018
DOI: 10.1016/j.htct.2017.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Hematological parameters, serum iron and vitamin B 12 levels in hospitalized Palestinian adult patients infected with Helicobacter pylori : a case–control study

Abstract: ObjectiveThis study aimed to investigate the relationship between hematological parameters, serum iron, and vitamin B12 levels in adult hospitalized Palestinian patients infected with Helicobacter pylori.MethodsThis case–control study included 150 adult (18–50 years old) patients infected with H. pylori and 150 healthy adults. A complete blood count was performed, and serum iron and vitamin B12 levels of the patients were measured, statistically analyzed and compared with the control group. All parameters in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 21 publications
7
29
1
Order By: Relevance
“…However, these changes seem to be reversible after H pylori eradication, due to an improvement in serum iron and vitamin B12 levels. [ 14 ] A special attention has been given to iron refractory iron-deficiency anemia (IRIDA) in the past years, as H pylori infection eradication has been proved to improve the efficacy of iron supplementation in various pediatric studies evolving around this condition. Still, a recent review that summarized the findings of multiple studies and randomized control trials on this matter, underlined the need for higher quality, larger cohort researches to elucidate a possible association between iron deficiency anemia and H pylori infection in children.…”
Section: Introductionmentioning
confidence: 99%
“…However, these changes seem to be reversible after H pylori eradication, due to an improvement in serum iron and vitamin B12 levels. [ 14 ] A special attention has been given to iron refractory iron-deficiency anemia (IRIDA) in the past years, as H pylori infection eradication has been proved to improve the efficacy of iron supplementation in various pediatric studies evolving around this condition. Still, a recent review that summarized the findings of multiple studies and randomized control trials on this matter, underlined the need for higher quality, larger cohort researches to elucidate a possible association between iron deficiency anemia and H pylori infection in children.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they observed a significant correlation between administration of anti‐ H pylori treatment plus iron and improvement of hemoglobin ( P < .001), MCV ( P < .001), iron ( P < .001), and ferritin levels ( P < .001) . Mwafy et al investigated 150 H pylori ‐positive patients (18‐50 years old) and 150 matched controls for several hematologic parameters, and they found significantly lower levels of iron in infected patients compared to uninfected (71.6 ± 24.8 vs 80.1 ± 20.7 μg/dL) and similar results were obtained for vitamin B12 levels (262.5 ± 100 vs 378.2 ± 160.6 pg/mL) . Nevertheless, Tseng et al, who followed up 508 patients with IDA, did not report any significant difference on hemoglobin levels between those treated or not treated for H pylori after a 2‐year observation but that could also be due to the presence of intestinal metaplasia .…”
Section: Hematologic Diseasesmentioning
confidence: 99%
“…A probable risk relationship between H. pylori infection and pernicious anemia was also suggested[ 47 ]. Case-control and prospective cohort studies have shown that patients with positive H. pylori had lower Vitamin B12 (Cobalamin) levels when compared to control groups[ 47 , 48 ]. In addition, when treated with triple therapy - clarithromycin, amoxicillin and omeprazole - to eradicate H. pylori , patients with previous pernicious anemia obtained satisfactory levels of Vitamin B12, with mean iron levels of 262.5 ± 100.0 pg/mL among H. pylori -positives against 378.2 ± 160.6 pg/mL in the group of H. pylori -negatives, representing a difference of 30.6% between those groups, with a P value of 0.001[ 48 ].…”
Section: Extragastric Manifestationsmentioning
confidence: 99%
“…Case-control and prospective cohort studies have shown that patients with positive H. pylori had lower Vitamin B12 (Cobalamin) levels when compared to control groups[ 47 , 48 ]. In addition, when treated with triple therapy - clarithromycin, amoxicillin and omeprazole - to eradicate H. pylori , patients with previous pernicious anemia obtained satisfactory levels of Vitamin B12, with mean iron levels of 262.5 ± 100.0 pg/mL among H. pylori -positives against 378.2 ± 160.6 pg/mL in the group of H. pylori -negatives, representing a difference of 30.6% between those groups, with a P value of 0.001[ 48 ]. Corroborating to the consolidation of this association, studies have shown that there is a decrease in Cobalamin levels in H. pylori positive patients regardless of gastric atrophy and dyspepsia[ 49 ].…”
Section: Extragastric Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation